Implementasi SAK EMKM Dalam Penyusunan Laporan Keuangan Studi Kasus pada Toko Gloria di Tulungagung - Siti Azizjah; Sri Dwi Estiningrum (Universitas Veteran Bangun Nusantara, 2022)
The preparation of financial statements has an important significance for a company, because it serves as an instrument to evaluate the financial condition and performance of the company as a whole. Toko Gloria, as a medium-sized business in the field of trade in groceries and beverages that are not prohibited, also needs to prepare financial reports in accordance with the Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). This is important so that the owner can obtain accurate information about the condition of the company. The purpose of this study is to investigate the preparation of financial statements based on SAK EMKM at Gloria stores in Tulungagung. This research is a case study using qualitative data and qualitative data analysis techniques. Several stages in the preparation of financial statements include designing codes and account names, making a list of fixed assets, preparing an initial trial balance, collecting transaction records, recording transactions in a special journal, posting to a ledger, preparing a trial balance, making adjusting journals, preparing a work balance. , preparation of financial reports, preparation of closing journal entries, and preparation of a trial balance after closing. The results of the study show that Gloria's shop does not compile complete financial reports. After using SAK EMKM, it is known that the Gloria store has an asset value of IDR 934,137,913.67, a liability value of IDR 372,512,000.00, an equity value of IDR 561,625,913.67, and a net profit of IDR 41,384. 190.00